2015
DOI: 10.1007/s12035-015-9580-9
|View full text |Cite
|
Sign up to set email alerts
|

Creatine, Similar to Ketamine, Counteracts Depressive-Like Behavior Induced by Corticosterone via PI3K/Akt/mTOR Pathway

Abstract: Ketamine has emerged as a novel strategy to treat refractory depression, producing rapid remission, but elicits some side effects that limit its use. In an attempt to investigate a safer compound that may afford an antidepressant effect similar to ketamine, this study examined the effects of the ergogenic compound creatine in a model of depression, and the involvement of phosphatidylinositol-3-kinase/protein kinase B/mammalian target of rapamycin (PI3K/Akt/mTOR) pathway in its effect. In order to induce a depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(68 citation statements)
references
References 85 publications
4
63
0
1
Order By: Relevance
“…Time ( (R)-ketamine. In the present study, whereas both (R)-ketamine and (S)-ketamine exerted long-lasting antidepressant effects even when they were no longer present in the brain and CSF, only (R)-ketamine exerted sustained antidepressant effects in the repeated CORT treatment model, in which reduced synaptic plasticity has been reported (Pazini et al, 2016). Therefore, the difference in the potency of the effects on synaptic plasticity may be responsible for the differences in the sustained antidepressant effects.…”
Section: Dosementioning
confidence: 46%
“…Time ( (R)-ketamine. In the present study, whereas both (R)-ketamine and (S)-ketamine exerted long-lasting antidepressant effects even when they were no longer present in the brain and CSF, only (R)-ketamine exerted sustained antidepressant effects in the repeated CORT treatment model, in which reduced synaptic plasticity has been reported (Pazini et al, 2016). Therefore, the difference in the potency of the effects on synaptic plasticity may be responsible for the differences in the sustained antidepressant effects.…”
Section: Dosementioning
confidence: 46%
“…c shows the notable CCs of neurons that may be regulated by target genes predicted using fold enrichment Table 5 The signaling pathways that may be regulated by targeted genes of the differentially expressed rno_circRNA_014900(p < 0.05) signaling, dopaminergic synapses, mTOR signaling, p53 signaling, apoptosis, MAPK signaling, TGF-beta signaling, axon guidance, Hippo signaling, etc.. These signaling pathways may be involved in the occurrence and development of depression, because some researches found that the Wnt signaling pathway played important roles in the depression-like behaviors [26][27][28], the PI3K-Akt signaling pathway was related to the rapid antidepressant-like effects of some drugs [29][30][31][32][33].…”
Section: Discussionmentioning
confidence: 99%
“…Previous study has revealed that autophagy contributes to synaptic plasticity and other brain functions through PI3K–Akt–mTOR pathway inhibition (Shehata et al, 2012). Another study found that creatine and ketamine can reverse depressive-like behavior and the underlying mechanism is through regulation of the PI3K/AKT/mTOR pathway, and modulation of synaptic proteins and BDNF in the hippocampus (Pazini et al, 2015). Currently, it has been discovered that stressful events could affect BDNF expression level in hippocampal thus induce depressive phenotypes.…”
Section: Discussionmentioning
confidence: 99%